The Effect of the Project-Based Learning Model Based on Entrepreneurship Professional Learning Community (PJBL-EPLC) with a Deep Learning Approach on Enhancing Critical Thinking Skills and Entrepreneurial Attitudes - Elta Resmawati; Siti Darwa Suryani (Lembaga Penelitian dan Pengembangan Sumberdaya Wilayah (elrispeswil), 2026)
The low level of students’ critical thinking skills and entrepreneurial attitudes in biology learning indicates the need for a contextual and meaningful learning model. This study aims to examine the effect of the Project-Based Learning model based on an Entrepreneurship Professional Learning Community (PjBL-EPLC) with a Deep Learning approach on students’ critical thinking skills and entrepreneurial attitudes at SMAN 2 Bengkulu City. This study employed a quasi-experimental method with a pretest-posttest nonequivalent control group design. The sample consisted of two classes, each with 36 students, selected using purposive sampling. The instruments included a critical thinking test and an entrepreneurial attitude questionnaire. Data were analyzed using inferential statistics based on prerequisite test results. The findings revealed significant differences in critical thinking skills (p = 0.006) and entrepreneurial attitudes (p = 0.001) between the experimental and control groups. These results indicate that the PjBL-EPLC model with a Deep Learning approach is more effective in improving students’ critical thinking skills and entrepreneurial attitudes compared to conventional learning.